Engineering the Optical Response of the Titanium-MIL-125 Metal–Organic Framework through Ligand Functionalization - Hendon, Christopher H; Tiana, Davide; Fontecave, Marc; Sanchez, Clément; D’arras, Loïc; Sassoye, Capucine; Rozes, Laurence; Mellot-Draznieks, Caroline; Walsh, Aron (Journal of the American Chemical Society, 2013)
Herein we discuss band gap modification of MIL-125, a TiO2/1,4-benzenedicarboxylate (bdc) metal–organic framework (MOF). Through a combination of synthesis and computation, we elucidated the electronic structure of MIL-125 with aminated linkers. The band gap decrease observed when the monoaminated bdc-NH 2 linker was used arises from donation of the N 2p electrons to the aromatic linking unit, resulting in a red-shifted band above the valence-band edge of MIL-125. We further explored in silico MIL-125 with the diaminated linker bdc-(NH 2 ) 2 and other functional groups (−OH, −CH3, −Cl) as alternative substitutions to control the optical response. The bdc-(NH 2 ) 2 linking unit was predicted to lower the band gap of MIL-125 to 1.28 eV, and this was confirmed through the targeted synthesis of the bdc-(NH 2 ) 2 -based MIL-125. This study illustrates the possibility of tuning the optical response of MOFs through rational functionalization of the linking unit, and the strength of combined synthetic/computational approaches for targeting functionalized hybrid materials.